Gynura procumbens (Lour.) Merr. Leaves Against Mice’s Antibody Titer - Rahimatul Uthia; Elin Resti Ananda; Ifora Ifora (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2019)
The body's defense system can be enhanced by certain compounds that are immunostimulant. An antibody titer is a measure of the body's level of immunity to a disease. Titers are usually expressed in terms of the number of times they can thin the blood until they cannot find any more antibodies. This study aims to determine the activity of the extracts of the leaves of Gynura Procumbens (Lour.) Merr. against antibody titers, the number, and percentage of leukocyte cells of white male mice. 25 mice were divided into 5 groups consisting of negative control, positive control, group dose 75 mg/kg body weight, 150 mg/kg body weight, 300 mg/kg body weight. The extract is given for 7 days orally. The results showed that the administration of leaf extracts can increase antibody titers and increase with increasing doses, as well as increasing the total number of leukocytes and the percentage of leukocyte cells significantly (P <0.05).